Molecular dynamics simulation of inter-molecular interactions : a thesis submitted to Massey University in Albany, Auckland in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Computational Biochemistry - Shadfar, Shamim Zahra (Massey University, 2019)
Many aspects of the operation of chemical and biological systems are based on intermolecular interactions. In this work, binding modes and interactions between molecules at a range of scales have been studied, using molecular dynamics (MD) simulations. The first chapter provides an introduction of each of the different chemical and biological systems that are studied in this work. It also introduces MD and its role in the context of this research. The second chapter corresponds to the study of host-guest interactions for cyclodextrin- bullvalene complexes. Bullvalene is a shapeshifter molecule, which interconverts between different isomers at room temperature. The goal of this chapter is to capture one favourable isomer of bullvalene (guest molecule) by binding it to cyclodextrin as a host molecule. This chapter consists of two smaller chapters (2i and 2ii). The former details the development and validation of a “host-guest binding potential energy profiling” (HGBPEP) method, which is a rotational interaction energy screening method designed for prediction of the most favourable orientation and position of bullvalene isomers with respect to cyclodextrin. The latter investigates the interaction of bullvalene isomers and cyclodextrin molecules, and finally binding free energy values of the complexes are calculated. The third chapter describes KstR, a transcriptional repressor in Mycobacteria. KstR is required for Mycobacterium tuberculosis (Mtb) pathogenesis as well as regulating the initial steps in cholesterol degradation by controlling the expression of the enzymes that carry out the early stages of cholesterol catabolism. Therefore, this protein is of great interest for development of new tuberculosis treatments. In this chapter, the stability and conformational changes of KstR in its different states – apo, DNA-bound and ligand-bound –have been studied. The main goal is to investigate the binding mechanism of KstR to DNA, as well as the effect of DNA and ligand binding on the structure and dynamics of KstR more generally, using MD simulations. In the fourth chapter, KstR2, another Mtb transcriptional repressor, is studied. KstR2 represses a 14-gene regulon involved in the later steps of cholesterol degradation. It is structurally similar to KstR, but has been proposed to act through a novel scissor-like mechanism. This chapter investigates two key questions regarding the mechanism of action of KstR2: first, the effect of mutating the key switch residue ARG170 to ALA, and second, the effect of ligand binding on its structure and motion. The focus of the fifth and final chapter is phosphatidylinositide 3-kinases (PI3Ks), which are proteins that take part in signalling pathways regulating factors like cell growth, survival and proliferation, which in turn are involved in cancer. The interaction between PI3Kα and another protein, RAS, is very important in the formation, growth and maintenance of RAS- driven tumours. A model of PI3Kα (class IA PI3K) has therefore been built, as well as of RAS associated with a model cell membrane, and MD simulations used to investigate the process by which the two proteins interact with one another and with the lipid bilayer. Altogether, this thesis uses MD simulations to provide insight into intermolecular interactions at a range of scales, with a particular focus on proteins involved in tuberculosis and in cancer.
Keywords: Intermolecular forces; Molecular dynamics; Simulation methods; Proteins; Tuberculosis; Cancer; Molecular aspects; 310109 Proteomics and intermolecular interactions (excl. medical proteomics)